2018
DOI: 10.6018/sportk.342941
|View full text |Cite
|
Sign up to set email alerts
|

Inluencia de distintos materiales didácticos acuáticos sobre la competencia percibida en el medio acuático por alumnos de segundo ciclo de educación infantil

Abstract: El presente trabajo pretendió comprobar qué material didáctico resultaba más eficaz para el desarrollo de la competencia percibida en el medio acuático en niños de 4 años. A tal fin, se aplicó la Escala Pictórica de Competencia Acuática Percibida (Moreno & Ruiz, 2008), antes y después de un programa de iniciación al medio acuático. En él, se utilizaron como variables independientes tres materiales didácticos de distintas características (Manguitos, Cinturón de flotación y Kiflot),y se contó con una muestra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
1
0
Order By: Relevance
“…However, the inclusion in the experimental group of motor games designed to develop the children's knowledge of their own bodies, the children in this group obtained moderately better results than the controls. Arguably, however, despite such games not being included in the control group's programme, the teaching of swimming itself often involves the use of specific body segments, underlined by the teachers, such that part of this work is already covered in conventional aquatic motor games (Gosálvez & Joven, 2014;Quintanilla-Bautista et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the inclusion in the experimental group of motor games designed to develop the children's knowledge of their own bodies, the children in this group obtained moderately better results than the controls. Arguably, however, despite such games not being included in the control group's programme, the teaching of swimming itself often involves the use of specific body segments, underlined by the teachers, such that part of this work is already covered in conventional aquatic motor games (Gosálvez & Joven, 2014;Quintanilla-Bautista et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the effects of swimming programmes for pre-schoolers have reported evidence that swimming is a valuable tool for individuals' holistic development (Quintanilla-Bautista, Simón-Piqueras, León-González, & Contreras Jordán, 2018). This holistic development covers aspects linked to child safety in aquatic environments (Langendorfer, 2011;Langendorfer, Moran, & Stallman, 2018;Moran & Gilmore, 2018), the development of motor skills and competences (Juárez, Osvaldo Rocca, Navandar, & Murcia, 2022;Pratt, Duncan, Morris, & Oxford, 2021;Simón-Piqueras, Prieto-Ayuso, Gómez-Moreno, Martínez-López, & Gil-Madrona, 2022) and factors related to the beneficial effects of such interventions based on salutogenic and personal well-being approaches (McCuaig, Quennerstedt, & Macdonald, 2013;Mittelmark & Bauer, 2022;Willcox-Pidgeon, Peden, & Scarr, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proof of the above-described concept is the important role that is generally given to the adequate mastery of skills related to awareness of the aquatic environment for the acquisition of more complex skills [ 12 , 36 , 37 ]. In this sense, this importance is not only affected from the motor point of view, but from other aspects such as confidence, autonomy and competence [ 38 ]. A student who is perceived as competent will be more autonomous, and the consequence is that he/she explores and interacts with the environment in a safer and more confident way [ 7 , 8 , 15 , 39 ].…”
Section: Discussionmentioning
confidence: 99%